2004
DOI: 10.3201/eid1005.030579
|View full text |Cite
|
Sign up to set email alerts
|

SARS in Hospital Emergency Room

Abstract: Thirty-one cases of severe acute respiratory syndrome (SARS) occurred after exposure in the emergency room at the National Taiwan University Hospital. The index patient was linked to an outbreak at a nearby municipal hospital. Three clusters were identified over a 3-week period. The first cluster (5 patients) and the second cluster (14 patients) occurred among patients, family members, and nursing aids. The third cluster (12 patients) occurred exclusively among healthcare workers. Six healthcare workers had cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
150
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(163 citation statements)
references
References 11 publications
8
150
0
4
Order By: Relevance
“…Thus, RNA of SARS-CoV was found on different environment samples, such as chair, elevator, computer mouse, etc ., and this may have contributed to contamination of health-care workers who had not been in direct contact with SARS-patients [109,110]. …”
Section: Hcovs: Enveloped But Not That Fragilementioning
confidence: 99%
“…Thus, RNA of SARS-CoV was found on different environment samples, such as chair, elevator, computer mouse, etc ., and this may have contributed to contamination of health-care workers who had not been in direct contact with SARS-patients [109,110]. …”
Section: Hcovs: Enveloped But Not That Fragilementioning
confidence: 99%
“…The high mortality rate of the disease and its easy transmission to health care workers characterize its clinical importance (1,10,12,13). The clinical manifestations, laboratory findings, radiologic presentations, and outcomes of SARS for patients have been well described (3,9,12).…”
mentioning
confidence: 99%
“…On April 27th, Hospital C found that a 73-year-old patient who had been kept in a regular ward for five days developed lung infiltrate. After immediate investigation, clinicians discovered that this patient had been to Hospital A on April 16th, but no agency informed them about the connection (Chen et al 2004c). By the time of discovery, a new cluster of SARS patients was already initiated by the patient.…”
Section: Low Local Sensitivity Triggeringmentioning
confidence: 96%
“…But after mid-April, a municipal hospital in Taipei (hereafter referred to as Hospital A 2 ) reported having a SARS hospital outbreak. Six other hospitals subsequently reported incidents of hospital-acquired or nosocomial infection that were all traced back to Hospital A (Chen et al 2004c, Chu et al 2005. In this phase of hospital outbreaks, the number of SARS cases soared dramatically from the low 30s to more than 400 (Yip et al 2007).…”
Section: Research Settingmentioning
confidence: 96%
See 1 more Smart Citation